Enhancement of Students’ Knowledge Regarding Appropriate Sunscreen Selection Based on SPF Variations and Skin Type Characteristics at Wirahusada Health Vocational School, Medan - Gratia Apulina Cindylawsa Purba; Anggun Syafitri; Ageng Azhar Amar; Hazimah Fithryyah Mardatillah; Agnes Clara Tamba (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Excessive exposure to ultraviolet (UV) radiation can cause various adverse effects on the skin, including erythema, premature skin aging, and an increased risk of skin cancer. One of the most effective preventive measures is the proper use of sunscreen selected according to its Sun Protection Factor (SPF) value and individual skin characteristics. However, adolescents' knowledge regarding appropriate sunscreen selection remains limited. This community service program aimed to improve students' knowledge and awareness of selecting appropriate sunscreen based on SPF variation and skin type characteristics. The program employed a participatory educational approach through health education sessions, interactive discussions, demonstrations, and skin condition assessments using a skin analyzer. The activity was conducted at Wirahusada Health Vocational High School, Medan, involving 20 students as participants. The educational materials covered UV radiation, skin types, SPF classification, sunscreen types, and the correct application of sunscreen. Skin condition assessments were performed to determine participants' skin moisture levels as the basis for providing appropriate sunscreen recommendations. The assessment results revealed that 11 participants (55.5%) had normal skin moisture, 7 participants (35.0%) had dry skin, and 2 participants (10.0%) had moist skin. Throughout the program, participants demonstrated high enthusiasm and active engagement during the educational sessions and discussions. The integration of health education with skin condition assessment effectively enhanced participants' understanding of selecting sunscreen according to their individual skin characteristics. Overall, this community service program successfully improved students' knowledge and awareness regarding the appropriate use of sunscreen as an essential strategy for protecting skin health from the harmful effects of ultraviolet radiation.